Durability of a New Thermal Aerogel-Based Rendering System under Distinct Accelerated Aging Conditions - Joana Maia (2021)
The widespread application of innovative thermal enhanced facade solutions requires an adequate durability evaluation. The present work intends to assess the durability of a new aerogel cement-based rendering system through the adaptation of different accelerated aging cycles, such as heating-freezing, freeze-thawing, and heat-cold. Several mechanical properties and also capillary and liquid water absorptions were tested for uncoated and coated specimens. A decrease in the mechanical strength, especially after freeze-thaw cycles, was observed. However, the water action promoted the late hydration of the cement paste contributing to the densification of the matrix and, consequently, the increase of the adhesive strength. Additionally, a decrease in the dynamic modulus of elasticity and an increase in the Poisson's ratio were observed after aging, which indicates a higher capacity of the render to adapt to substrate movements, contributing to a reduction of cracking.